2013
DOI: 10.1038/hdy.2013.63
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis and evolution of 5S ribosomal DNA in metazoans

Abstract: Several studies on 5S ribosomal DNA (5S rDNA) have been focused on a subset of the following features in mostly one organism: number of copies, pseudogenes, secondary structure, promoter and terminator characteristics, genomic arrangements, types of non-transcribed spacers and evolution. In this work, we systematically analyzed 5S rDNA sequence diversity in available metazoan genomes, and showed organism-specific and evolutionary-conserved features. Putatively functional sequences (12 766) from 97 organisms al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 80 publications
4
32
0
1
Order By: Relevance
“…We predicted the secondary structure of the five U1 snDNA consensus sequences, as this can be an indicator of its functionality or pseudogenicity (Figure 6b). Lineages 1 and 2 contained the four conserved sites described in Vierna et al (2013) (Figure 6b), and they showed the same pattern, with four helices, as the consensus secondary structure of U1 snRNA reported in Vierna et al (2013). The secondary structure of lineage 1 showed higher stability (ΔG = − 56.0 kcal mol − 1 ) than lineage 2 (ΔG = − 54.6 kcal mol − 1 ).…”
Section: Chromosomal Mapping Of U1 Sndnasupporting
confidence: 57%
See 2 more Smart Citations
“…We predicted the secondary structure of the five U1 snDNA consensus sequences, as this can be an indicator of its functionality or pseudogenicity (Figure 6b). Lineages 1 and 2 contained the four conserved sites described in Vierna et al (2013) (Figure 6b), and they showed the same pattern, with four helices, as the consensus secondary structure of U1 snRNA reported in Vierna et al (2013). The secondary structure of lineage 1 showed higher stability (ΔG = − 56.0 kcal mol − 1 ) than lineage 2 (ΔG = − 54.6 kcal mol − 1 ).…”
Section: Chromosomal Mapping Of U1 Sndnasupporting
confidence: 57%
“…The analysis for sequence diversity was conducted using DNASP v5.10 (Librado and Rozas, 2009) excluding positions with gaps in the alignments. The G+C content was calculated with the MEGA v5.0 (Tamura et al, 2011) software, and the prediction of secondary structure and Gibbs free energy (ΔG) for the different sequence lineages was performed with RNAFold (Hofacker, 2003), applying a constrained folding to avoid the pairing of the four conserved motifs, according to Vierna et al (2013).…”
Section: Chromosomes Probes and Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the presence of linked and unlinked signals in species belonging to the family Bucephalidae is in accordance with results obtained from other organisms. The presence of 5S rDNA linked to other multigene families, including major rDNA, is a common situation in fungi, nematodes, and crustaceans [Drouin and de Sá, 1995;Vierna et al, 2013]. The study of the molecular organization of the linked tandem arrays in those groups demonstrated that, at least in some cases, closely related species showed differences in both tandem arrangement and gene orientation and led to suggestions that those 5S rRNA gene linkages were repeatedly established and lost during the evolution of their genomes [Drouin and de Sá, 1995;García and Kovařík, 2013].…”
Section: Overlapping and Separated Major And 5s Rdna Signalsmentioning
confidence: 99%
“…As expected, we have observed a significantly higher number of virus-mapping reads in the adult female library where rRNA was depleted with RiboMinus TM treatment (dataset "Schwaiger et al rRNA-depleted") when compared to the rest of the datasets. However, it needs to be taken into account that commercially available probes used for rRNA depletion are not designed for non-bilaterian animals and are less efficient in depleting the 5S small ribosomal subunit due to its high sequence variability between different animal phyla [50], which might compromise the library depth available to low-frequency viruses. Therefore, a truly unbiased search for RNA viruses would certainly gain from an rRNA depletion method custom-fitted for N. vectensis sequences.…”
Section: Discussionmentioning
confidence: 99%